The effect of addition Eriobotrya japonica L. marmalade on physicochemical, microbiological, and sensory properties of probiotic yogurts - Turgut, Tamer; Diler, Abdulkerim (Frontiers in Nutrition, 2023)
This study investigated the effects of loquat (Eriobotrya japonica L.) marmalade (LM) supplementation in probiotic yogurt during a 21 days storage period. In addition, the viability of Bifidobacterium and its effect on yogurt quality were investigated. Four types of yogurt, including plain yogurt (LM0) and yogurts with 5%, 10%, and 15% LM, were prepared. On days 1, 7, 14, and 21 of storage, physicochemical properties, microbial growth, and textural and sensory properties were investigated. The addition of LM to yogurt significantly affected the total dry matter, fat, pH, titratable acidity, syneresis, water holding capacity, and color parameters (L*, a*, b*). The addition of LM caused a decrease in L* (from 87.52 to 81.78) and an increase in a* values (from −35.42 to −30.14). Yogurts containing 10 and 15% LM demonstrated lower syneresis than control samples during storage. During storage, the pH of yogurts continuously decreased (P < 0.01). The viability of Bifidobacterium in yogurt was not affected by the LM addition. During storage, the viable count of Bifidobacterium ssp. decreased in all yogurt types. Lactobacillus delbrueckii ssp. bulgaricus decreased more than Streptococcus thermophilus did during storage. In all yogurt samples, coliform bacteria stayed below detectable concentrations. When a general evaluation was made by considering the physicochemical quality, sensory, and textural properties of all yogurt samples, it was revealed that LM-added yogurts can be produced and stored for 21 days.